RISK FACTORS FOR KNEE PAIN IN FEMALE DIABETES MELLITUS PATIENTS AGED ≤ 45 YEARS - Lina, Nur; Novianti, Siti; Faturahman, Yuldan (UNG, 2025)
Diabetes Mellitus (DM) and Osteoarthritis (OA) coexist in the same population. Women with DM and OA have a higher prevalence of knee pain. Objective: to analyze knee pain in female DM patients aged ≤ 45 years. The research method uses a cross-sectional research design. The sample is the entire population, namely women diagnosed with DM aged ≤ 45 years in Cilacap Regency. Measurement of Knee Pain Degree using the Womac Index. The results of the study were that the average pain score of the respondents was 7.87, the stiffness score was 3.84 and the physical disorder score was 19.23. The average total score of pain, stiffness and functional impairment was 39.22. There was an association between Obesity PR = 8.77 (95% CI 3.23-23.79) and blood pressure PR 3.89(95% CI 1.67-9.07) with the degree of knee pain in female DM patients ≤ 45 years of age. The conclusion was that 41.51% of respondents experienced pain, stiffness and mild functional disorders and 58.49% moderate/severe.